Ultrastructure and histochemistry of the fat body of Anthonomus grandis (Coleoptera: Curculionidae). Issue 2 (2nd April 2016) - da Cunha, Franklin Magliano; Wanderley-Teixeira, Valéria; Teixiera, Álvaro Aguiar Coelho; Alves, Luiz C.
Abstract: Metabolic demands such as growth and reproduction of insects relate directly to the fat body. This organ is responsible for the biosynthesis and storage of nutrients, and participates in the neutralization and detoxification of xenobiotics. Studies show a relationship between its ability to accumulate nutrients and activities, such as diapause and reproduction in the beetle Anthonomus grandis, an important pest of cotton plants. However, there are no detailed studies on the structure and histochemistry of the fat body in this insect. We describe the ultrastructure and histochemistry of the fat body in A. grandis and discuss some of its characteristic features. The fat body is composed of a single cell type, the trophocyte, which is a voluminous cell with a spherical or bilobed nucleus, and cytoplasm containing several lipid droplets, glycogen granules (electron-dense), and protein granules. These trophocytes have few areas of contact with each other and form lobes, enclosed by connective tissue. A high metabolic activity of the fat body is deduced by the intense histochemical staining for protein and polysaccharide compounds, demonstrating that specific processes, such as the synthesis and secretion of vitellogenin, could be a target for more specific studies on methods to control this insect.